Study of Polyvinyl Alcohol-SiO(2) Nanoparticles Polymeric Membrane in Wastewater Treatment Containing Zinc Ions - Căprărescu, Simona (Polymers (Basel), 2021)
The main goal of the present paper was to synthesize the polyvinyl alcohol-SiO(2) nanoparticles polymeric membrane by wet-phase inversion method. The efficiency of prepared membranes (without and with SiO(2)) was investigated using a versatile laboratory electrodialysis system filled with simulated wastewaters that contain zinc ions. All experiments were performed at following conditions: the applied voltage at electrodes of 5, 10 and 15 V, a concentration of zinc ions solution of 2 g L(−1), time for each test of 1 h and at room temperature. The demineralization rate, extraction percentage of zinc ions, current efficiency and energy consumption were determined. The polymeric membranes were characterized by Fourier Transforms Infrared Spectroscopy-Attenuated Total Reflection (FTIR-ATR), Scanning Electron Microscopy (SEM) and Electrochemical Impedance Spectroscopy (EIS). The higher value of percentage removal of zinc ions (over 65%) was obtained for the polymeric membrane with SiO(2) nanoparticles, at 15 V. The FTIR-ATR spectra show a characteristic peak located at ~1078 cm(−1) assigned to the Si-O-Si asymmetrical stretching. SEM images of the polymeric membrane with SiO(2) nanoparticles show that the nanoparticles and polymer matrix were well compatible. The impedance results indicated that the SiO(2) nanoparticles induced the higher proton conductivity. The final polymeric membranes can be used for the removal of various metallic ions, dyes, organic or inorganic colloids, bacteria or other microorganisms from different natural waters and wastewaters.